Zastosowanie modeli strukturalnych do weryfikacji założeń programów unijnych - Bartkowiak, Anna (Verification of Assumptions of European Union Programmes by Using Structural Equations Models, 2007)
European Union Programmes consist of general objective and operational objectives. For verification of achievement of these objectives European Integration Committee choose monitoring indicators for each objective. Union's Programmes also assume that achievement of operational objectives influences achievement of general objective. Assumption of influence and choice of indicators is only intuitional and it is any statistical verification. Nature of programmes asumptions suggests possibility of use of one of latent variables model. In my article I verify choice of indicators and influence objectives by using SEM.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 15-30